Techniques to Study Antigen-Specific B Cell Responses - Boonyaratanakornkit, Jim; Taylor, Justin J. (Frontiers in Immunology, 2019)
Antibodies against foreign antigens are a critical component of the overall immune response that can facilitate pathogen clearance during a primary infection and also protect against subsequent infections. Dysregulation of the antibody response can lead to autoimmune disease, malignancy, or enhanced infection. Since the experimental delineation of a distinct B cell lineage in 1965, various methods have been developed to understand antigen-specific B cell responses in the context of autoimmune diseases, primary immunodeficiencies, infection, and vaccination. In this review, we summarize established techniques and discuss new and emerging technologies for probing the B cell response in vitro and in vivo by taking advantage of the specificity of B cell receptor-associated and secreted antibodies. These include ELISPOT, flow cytometry, mass cytometry, and fluorescent microscopy to identify and/or isolate primary antigen-specific B cells. We also present our approach to identify rare antigen-specific B cells using magnetic enrichment followed by flow cytometry. Once isolated, in vitro proliferation assays and adoptive transfer experiments in mice can be used to further characterize antigen-specific B cell activation, function, and fate. Transgenic mouse models of B cells targeting model antigens and of B cell signaling have also significantly advanced our understanding of antigen-specific B cells responses in vivo.